Strategies for Annulus Fibrosus Regeneration: From Biological Therapies to Tissue Engineering - Chu, Genglei; Shi, Chen; Wang, Huan; Zhang, Weidong; Yang, Huilin; Li, Bin (Frontiers in Bioengineering and Biotechnology, 2018)
Intervertebral disc (IVD) is an avascular tissue which contributes to the weight bearing, motion and flexibility of spine. However, IVD is susceptible to damage and even failure due to injury, pathology and aging. Annulus fibrosus (AF), the structural and functional integrity of which is critically essential to confine nucleus pulpous (NP) and maintain physiological intradiscal pressure under mechanical loading, plays a critical role in the biomechanical properties of IVD. AF degeneration commonly results in substantial deterioration of IVD. During this process, the biomechanical properties of AF and the balance between anabolism and catabolism in IVD are progressively disrupted, leading to chronic back pain and even disability of individuals. Therefore, repairing and regenerating AF are effective treatments to degeneration-associated pains. However, they remain highly challenging due to the complexity of natural AF tissue in the aspects of cell phenotype, biochemical composition, microstructure, and mechanical properties. Tissue engineering (TE), by combining biological science and materials engineering, shed lights on AF regeneration. In this article, we review recent advances in the pro-anabolic approaches in the form of cell delivery, bioactive factors delivery, gene therapy and TE strategies for achieving AF regeneration.